2014
DOI: 10.1039/c3cc49453e
|View full text |Cite
|
Sign up to set email alerts
|

Linker-determined drug release mechanism of free camptothecin from self-assembling drug amphiphiles

Abstract: We report here that the release mechanism of free camptothecin from self-assembling drug amphiphiles can be regulated by use of different linker groups. Our results highlight the significance of the linker group of drug amphiphiles on the drug release efficiency and their consequent in vitro efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 26 publications
1
73
0
Order By: Relevance
“…For example, one can use tethered drugs as cross-links in a hydrogel, with the network degradation itself facilitating the drug release. This approach can also minimize the use of excipients like cross-linkers and thus increase the drug loading 170 . A hetero-bifunctional PEG chain was tethered via the primary amines on BSA, forming a macromer cross-linked PEG hydrogel; by tuning the hydrolysis rate of ester bonds in the network via adjacent charged amino acids, the BSA was released over weeks 171 .…”
Section: Designing Across Length Scalesmentioning
confidence: 99%
“…For example, one can use tethered drugs as cross-links in a hydrogel, with the network degradation itself facilitating the drug release. This approach can also minimize the use of excipients like cross-linkers and thus increase the drug loading 170 . A hetero-bifunctional PEG chain was tethered via the primary amines on BSA, forming a macromer cross-linked PEG hydrogel; by tuning the hydrolysis rate of ester bonds in the network via adjacent charged amino acids, the BSA was released over weeks 171 .…”
Section: Designing Across Length Scalesmentioning
confidence: 99%
“…3335 DAs possess one hundred percent loading capacity, as well as the ability to optimize the delivery of the drug via a biodegradable linker. 36 This biodegradation is one of the key factors in the stability of the drug delivery vehicle, and resulting dissociation and delivery.…”
Section: Introductionmentioning
confidence: 99%
“…182 Taking this into consideration, Cui and co-workers investigated the drug release mechanism from their DA platform using two disulphide linkers—buSS and a disulfanyl-ethyl carbonate etcSS linker. 188 Results indicated that CPT-etcSS-Tau exhibited a faster release of free drug upon contact with GSH due to a more effective self-immolation mechanism upon reduction. This was reflected in the cytotoxic nature of the molecule as the CPT-etcSS-Tau demonstrated a much lower IC 50 value than the CPT-buSS-Tau, one much closer to free CPT.…”
Section: Small Molecule Sapdsmentioning
confidence: 96%